2018
DOI: 10.3390/nu10050655
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tea Consumption with Risk of Alzheimer’s Disease and Anti-Beta-Amyloid Effects of Tea

Abstract: Neurodegenerative disease Alzheimer’s disease (AD) is attracting growing concern because of an increasing patient population among the elderly. Tea consumption is considered a natural complementary therapy for neurodegenerative diseases. In this paper, epidemiological studies on the association between tea consumption and the reduced risk of AD are reviewed and the anti-amyloid effects of related bioactivities in tea are summarized. Future challenges regarding the role of tea in preventing AD are also discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 95 publications
(97 reference statements)
0
48
0
Order By: Relevance
“…Studies conducted worldwide confirm the existence of a correlation between drinking tea and positive effects on human cognitive function [14,17,36]. In their literature review, Polito et al [14] analyzed epidemiological data and concluded that drinking tea can reduce the risk of AD and other neurodegenerative diseases, as well as improve cognitive functions in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies conducted worldwide confirm the existence of a correlation between drinking tea and positive effects on human cognitive function [14,17,36]. In their literature review, Polito et al [14] analyzed epidemiological data and concluded that drinking tea can reduce the risk of AD and other neurodegenerative diseases, as well as improve cognitive functions in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted worldwide confirm the existence of a correlation between drinking tea and positive effects on human cognitive function [14,17,36]. In their literature review, Polito et al [14] analyzed epidemiological data and concluded that drinking tea can reduce the risk of AD and other neurodegenerative diseases, as well as improve cognitive functions in the elderly. Okello et al [37] demonstrated that green and black tea extracts can improve the efficiency of the cholinergic system, which may substantially contribute to alleviating the effects of the cholinergic deficit observed in AD and other age-related memory disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that their findings demonstrate that only Aβ(1-42) contains unique structural features that facilitate membrane insertion and channel formation, now aligning ion channel formation with the neurotoxic effect of Aβ(1-42) compared to Aβ in Alzheimer's disease [53]. (In addition, tea polyphenols have been repeatedly reported (e.g., [54]) to protect cells from Aβ-mediated neurotoxicity, by dose-dependently inhibiting the formation of Aβ aggregates (e.g., from fresh Aβ(1-42) peptides), through the destabilization of preformed Aβ aggregates. These green tea polyphenols (regularly ingested worldwide via tea beverage consumption) are considered to be valuable, for the prevention and therapeutic treatment of Alzheimer's disease, via the combined effect of inhibiting Aβ aggregate formation and protecting neurons from the toxicity (e.g., oxidative stress) induced by Aβ [54].…”
Section: Cardiovascular Risk Factors Inflammation Oxidative Stressmentioning
confidence: 99%